Determining the Hydrogen Sulfide Concentration at Tangkuban Perahu Mount Using TGS-2602 Sensor - Putra, Adiyasa Pratama; Alam Purnama, Atra Ardiyanto; Prihatini, Jihan; Adrian, Kristofer; Sawita, I Kadek Agus Sara; Evita, Maria; Djamal, Mitra (Institut Teknologi Bandung, 2025)
Indonesia is a country with numerous volcanoes which are a great hazard to people living in surrounding areas. As a result, eruption predictions and pre-emptive warnings are extremely important. In mount Tangkuban Perahu in particular, hydrogen sulfide is abundantly produced. By detecting hydrogen sulfide levels, volcanic activities in Tangkuban Perahu can be predicted and early warnings can be released to alert the people in the area. To obtain a reading of the concentration of hydrogen sulfide we use the TGS 2602 gas sensor equipped with Arduino to process the readings and ESP-32S to connect the system to IOT. This sensor system is equipped on a mobile robot which had been developed in previous research. Through field experiments, we have determined that our system has successfully obtained the readings of hydrogen sulfide in various parts of the day. Our readings showed that mount Tangkuban Perahu is safe and stable throughout the day with none of the average hydrogen sulfide reading in the morning, afternoon, and evening exceeding 0.3 ppm.